Hubungan Brand Equity dan Minat Konsumen: Studi Kasus Perubahan Merek Produk Elektronilk Nasional-Panasonic menjadi Panasonic - Petra Surya Mega Wijaya; Anita Puspitasari (Jurnal Riset Manajemen dan Bisnis, 2006)
It is known that brand has the power to attract consumer to buy a product or some services being represented. It also has the role to help the producers to achieve their sales target. Hence, construct a brand in a vigilant way is essential, prior to the competitive advantage that witl be gafned through it. Recently, there is a phenomenon when firms tend to reconstruct their old brand to o new brand name. In Indonesia, one of them is the case of the brand called National-Panasonic, which have been replaced by a new brand name Panasonic. The changing of theNational-Panasonic can obviously notice by the vanishing of this brand name in the Indonesia electronic market.Based on the cose of Panasonic, this research aim to examine the relationship between brand awareness, brand association, perceived quality, brand loyalty, and consumers' intention to buy. Furthermore this research also examines the relationship between brand equity and consumers intention to buy.For about 100 data were collected which comes fro* peoplereside in Surakarta-Central of Java, who have an experience on using the brand. Afterward the data are analyzed using the correlation method. The results show that brand awareness; brand association, perceived quality, brand loyalty, and brand equity are correlated with consumer's intention to buy.Keywords: Brand equity, brand owarness, brand loyalty, consumer's intention to buy